National self-interest in the cosmos: a regime analysis of outer space - Orr, Shannon (University of Guelph, 1997)
The intention of this thesis is to analyse outer space in the context of international regime theory from a neo-realist perspective, and to argue that, despite the prevailing structures and the existence of the United Nations Committee On Peaceful Uses of Outer Space (UNCOPUOS), a real international regime for outer space does not yet exist. Due to prevailing national self-interest, the Committee over the past forty years has demonstrated glaring inefficiencies which prevent the development of a real international regime such as that governing Antarctica and the open seas. Collective egoistic self-interest, it is argued, is one of the dominant explanations for behaviour in outer space, and can be understood to be the desire to maximize one's own utility function without regard for the utility of other state parties. This is demonstrated through studies of delimitation, military uses of outer space, the geostationary orbit, nuclear power sources, remote sensing, direct broadcasting and consensus.